PERANCANGAN SISTEM INFORMASI KANTOR CAMAT SIPOHOLON KABUPATEN TAPANULI UTARA BERBASIS WEB - Sion Sela Simorangkir; Roni Jhonson Simamora; Jamaluddin Jamaluddin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2022)
Technology is growing along with the increasing need to enter the world of globalization, we recognize increasingly advanced technology to make it easier to carry out various activities in life. The sub-district is a government organization consisting of several villages, with an information system in the Sipoholon sub-district will greatly assist the sub-district government in receiving or providing information to the public and to higher government agencies in a short time. Based on the existing problem, how to make a website information system at the Sipoholon sub-district office. Thus, a system is needed that can facilitate the process of efficient data information for sub-district employees in updating data without having to wait for data change reports about the Sipoholon sub-district office, make it easier for sub-district employees to process data and report news data, village announcements so that they can affect the optimization of the work process of sub-district employees.